A qualitative description of successful aging through different decades of older adulthood. (2nd December 2017) - Carr, Kelly; Weir, Patricia L.
ABSTRACT: Objective: To qualitatively examine factors that contribute to successful aging during different decades of older adulthood. Methods: Fundamental qualitative description was adopted as the methodological framework. Through purposeful sampling, 42 community dwelling older adults (mean age = 79.6 years, age range = 65–97 years; 19 males) were recruited. Focus groups (6) segmented by decade of life were conducted with participants 65–74 ( n = 17) and 75–84 ( n = 17) years of age. Semi-structured interviews (16) were conducted with four participants from each decade, as well as participants 85 years of age and older ( n = 8). Data analyses were conducted independently for each decade of life and included inductive analysis of textual data through continuous comparisons of meaning units. Results: Three primary themes related to successful aging were identified across all decades of older adulthood: (1) staying healthy (secondary themes: genetics and lifestyle choices ), (2) maintaining an active engagement in life (secondary themes: social engagement and cognitive engagement ), and (3) keeping a positive outlook on life . Participants in specific decades of older adulthood identified three additional secondary themes related to maintaining an active engagement in life : finances (65–74 and 85+ years), social support (75+ years), and successful marriage (75+ years). Similarly, only adults 65–84 years of age identified a secondary theme for keeping a positive outlook on life: acceptance and adaptation . Conclusion: Primary themes related to successful aging were agreed upon by participants in all decades of older adulthood, while age-based differences existed among secondary themes. Thus, what it means to age successfully may be age-dependent.